Drug Delivery Platforms Containing Thermoresponsive Polymers and Mucoadhesive Cellulose Derivatives: A Review of Patents - da Silva, Jéssica B.; dos Santos, Rafaela Said; Vecchi, Camila Felix; Bruschi, Marcos Luciano (Recent Advances in Drug Delivery and Formulation, 2022)
Nowadays, the development of mucoadhesive systems for drug delivery has gained keen interest, with enormous potential in applications through different routes. Mucoadhesion characterizes an attractive interaction between the pharmaceutical dosage form and the mucosal surface. Many polymers have shown the ability to interact with mucus, increasing the residence time of local and/or systemic administered preparations, such as tablets, patches, semi-solids, and micro and nanoparticles. Cellulose is the most abundant polymer on the earth. It is widely used in the pharmaceutical industry as an inert pharmaceutical ingredient, mainly in its covalently modified forms: methylcellulose, ethylcellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methylcellulose, and carboxymethylcellulose salts. Aiming to overcome the drawbacks of oral, ocular, nasal, vaginal, and rectal routes and thereby maintaining patient compliance, innovative polymer blends have gained the interest of the pharmaceutical industry. Combining mucoadhesive and thermoresponsive polymers allows for simultaneous in situ gelation and mucoadhesion, thus enhancing the retention of the system at the site of administration and drug availability. Thermoresponsive polymers have the ability to change physicochemical properties triggered by temperature, which is particularly interesting considering the physiological temperature. The present review provides an analysis of the main characteristics and applications of cellulose derivatives as mucoadhesive polymers and their use in blends together with thermoresponsive polymers, aiming at platforms for drug delivery. Patents were reviewed, categorized, and discussed, focusing on the applications and pharmaceutical dosage forms using this innovative strategy. This review manuscript also provides a detailed introduction to the topic and a perspective on further developments.
Keywords: hydroxypropyl cellulose